Clinical researchThe efficiency of a sedative or analgesic supplement to periprostatic nerve blockage for pain control during transrectal ultrasound-guided prostate biopsy – a prospective, randomized, controlled, double blind study - Ozok, Hakki U.; Sagnak, Levent; Ates, Mevlut A.; Karakoyunlu, Nihat; Topaloglu, Hikmet; Ersoy, Hamit (Archives of Medical Science, 2010)
Introduction : The aim was to examine the effect of a sedative or analgesic supplement to periprostatic nerve blockage (PNB) on pain reduction during probe insertion and needle penetration in patients undergoing transrectal ultrasound (TRUS)-guided prostate biopsy. We also investigated the effects of this procedure on the positive response rate in re-biopsy. Material and methods : One hundred TRUS-guided prostate biopsy patients due to prostate-specific antigen (PSA) levels higher than 2.5 ng/ml and/or abnormal rectal examination findings were evaluated. Group 1 (PNB) was given periprostatic lidocaine injection before the procedure. Group 2 (analgesic) was given tramadol and PNB. Group 3 (sedative) was given midazolam and PNB. Group 4 (control) was not given any anaesthesia or analgesics. Pain scores were assessed during probe insertion and needle penetration by a visual analogue scale. Results : During probe insertion, the mean pain score of the sedative group was lower than that of the control, analgesic and PNB groups (p < 0.001, p = 0.009, and p < 0.001, respectively). During needle penetration, the mean pain score of the control group was higher than that of the other groups (p < 0.001). The rate of positive response to re-biopsy was found to be 56% in the control group and between 92% and 100% in the other three groups (p < 0.001). Conclusion : According to our results, it can be concluded that midazolam, given supplementary to PNB, contributes as an effective and safe alternative for pain control during both probe insertion and penetration of the biopsy needle into the prostate capsule; however, tramadol supplement does not provide any additional contributions.